Liever geen beeld van Petrus Regout. Bedrijfsjubilea van de Sphinx - Cillekens, Caspar (Studies over de sociaaleconomische geschiedenis van Limburg, 2020)
Company anniversaries are excellent opportunities to renew the bond with the workforce and the wider world. They are also occasions for reflections about the company’s past, unwelcome as they may be. In the 20th century, the management of the Maastricht ceramics company De Sphinx had great difficulty setting the stage for its anniversaries. With waves of redundancies etched in people’s memory, the times did not seem ripe in the 1930s and 1980s for high-profile festivities. Interestingly, the initiative for celebrating the company’s 125th anniversary in 1959 was not taken by the management, but by three company foremen. They felt that the Regout family could no longer disregard a celebration. In this article, I shall examine why the company management feared the resurgence of old controversies and was reluctant to celebrate anniversaries. Curiously, the population of Maastricht, often critical of De Sphinx, was also hostage to the past.